Kapal Kecil yang Efisien di Perairan Berlumpur dan Dangkal - Rengi, Pareng; Hutauruk, Mangasi (Jurnal Perikanan dan Kelautan, 2016)
Indonesian has more shallow and muddy waters as well as narrow rivers with hyacinth caused waters explorations to be inhibited. Ordinary transportation is incapable to conduct profound activities then special small vessels is required to be operated in that area. To achieve the goal, the vessel is designed by using some surveys to many of waters samplings to acquires the required vessel draft. Thus, ship propulsion systems will be not distructed to produce trust. The breadth of the rivers is made as parameters in determining ship breadth then be optimized by various dimension of ship comparison. The dimension of new vessel is L = 2,15 m, B = 0,75 m, H = 0,40 m and T = 0,15 m where the power of engine is 6 PK,with reverse system. Ship performance quite good from numerical simulation view.